PPI partnerships versus PPI divorces in LDCs (or are we switching from PPPI to PPDI?) - Estache, Antonio (World Bank, Washington, DC, 2012)
Thirty years ago, in 1974, Chile launched the first large-scale privatization in a developing country. About 15 years later, Argentina provided a new model of global infrastructure management. Since then a variety of public-private partnerships in infrastructure have been adopted throughout the developing and transition world. These experiences add up to a large and heterogeneous enough sample of experiences from which some fairly robust conclusions on who benefited from the reforms and who did not. Because many of these experiences are also turning sour and the "privatization" fad of the 1990s seems to be turning into an "anti-privatization" fad, it seems important to separate facts from emotions. The author argues that the wide differences in interpretations of the facts can be explained by wide differences in the assessment criteria used by analysts, including the definition of the baseline data chosen to assess the incremental effect of reforms. It is also driven by the sectors, the regions, and probably most important, the actors on which the analysis tends to focus. Once all these factors have been considered, a relatively fair and quantitative assessment of the prospects of the public-private relationship in infrastructure is possible.